Structural Changes in Prothrombin during Activation: A Theory - Seegers, Walter H.; Murano, Genesio; McCoy, Lowell (Thrombosis and Haemostasis, 1970)
Properties of the thrombin zymogen are quite different when in the form of prothrombin complex, DEAE-prothrombin (prothrombin) or prethrombin. When removed from the prothrombin complex, prothrombin spontaneously became refractory to the two-stage analytical reagents. No new N-terminal amino acids formed in association with this activation. A first step in prothrombin activation might be related to conformation. Repeatedly one mole of alanine was found as N-terminal amino acid for prothrombin and it is thus a single chain protein. Prethrombin did not have this alanine, but lysine and threonine, were found. Prethrombin, like thrombin, thus had two chains. After the conversion of prethrombin to thrombin with purified autoprothrombin C, a new N-terminal alanine amino acid was found attached to a peptide. Additionally peptides with N-terminal serine, lysine, and glycine were found. Threonine and isoleucine were again found as the N-terminal amino acids for 3.7 S thrombin and 3.2 S thrombin. As a working hypothesis, a perspective on the possible structure of prothrombin is outlined on the basis that it contains two moles of thrombin. Prethrombin probably forms when Ala1-peptide splits from a polypeptide chain which forms a loop held together by a disulfide bridge. Proteolysis probably also occurs in this loop. The postulated disulfide bridge would be the one which holds the A and B chains of thrombin together. In the conversion of prethrombin to thrombin, the first mole of thrombin would be set free. Then the Ala2-peptide released might correspond to the Ala1-peptide removed when prethrombin originally formed. Ala2-peptide thus would be related to the second mole of thrombin which could arise by further proteolysis including a split in the loop held together by a disulfide bridge. It is postulated that acidic peptides are attached to the main prothrombin polypeptide chain, to prethrombin, and to 3.7 S thrombin as satellite material.